Colchicine Does Not Reduce Abdominal Aortic Aneurysm Growth in a Mouse Model. (30th September 2022) - Phie, James; Thanigaimani, Shivshankar; Huynh, Pacific; Anbalagan, Raghuveeran; Moran, Corey S.; Kinobe, Robert; Moxon, Joseph V.; Field, Matt A.; Krishna, Smriti M.; Golledge, Jonathan
Abstract : Background and Aims . The nacht domain, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3) inflammasome is upregulated in human abdominal aortic aneurysm (AAA), but its pathogenic role is unclear. The aims of this study were firstly to examine whether the inflammasome was upregulated in a mouse model of AAA and secondly to test whether the inflammasome inhibitor colchicine limited AAA growth. Methods . AAA was induced in eight-week-old male C57BL6/J mice with topical application of elastase to the infrarenal aorta and oral 3-aminopropionitrile (E-BAPN). For aim one, inflammasome activation, abdominal aortic diameter, and rupture were compared between mice with AAA and sham controls. For aim two, 3 weeks after AAA induction, mice were randomly allocated to receive colchicine (n = 28, 0.2 mg/kg/d) or vehicle control (n = 29 ). The primary outcome was the rate of maximum aortic diameter increase measured by ultrasound over 13 weeks. Results . There was upregulation of NLRP3 markers interleukin- (IL-) 1 β (median, IQR; 15.67, 7.11-22.60 pg/mg protein versus 6.87, 4.54-11.60 pg/mg protein, p = .048 ) and caspase-1 (109, 83-155 relative luminosity units (RLU) versus 45, 38-65 RLU, p < .001 ) in AAA samples compared to controls. Aortic diameter increase over 80 days (mean difference, MD, 4.3 mm, 95% CI 3.3, 5.3, p < .001 ) was significantly greater in mice in which aneurysms were induced compared to sham controls. Colchicine did not significantly limit aortic diameter increase over 80 days (MD -0.1 mm, 95% CI -1.1, 0.86, p = .922 ). Conclusions . The inflammasome was activated in this mouse model of AAA; however, daily oral administration of colchicine did not limit AAA growth.